Hyaluronic acid covalently grafted graphene oxide stably targets the natural cartilage friction interface for achieving long-term wear resistance - Yuan, Ziji; Ma, Teng; He, Xiaofan; Fang, Ying; Wu, Liangbin; Wu, Qian; Li, Chuanrun; Peng, Chengjun; Wu, Bo (Wear, 2025)
The exploitation of long-acting intra-articular lubricants is significantly important for the treatment of early osteoarthritis. Herein, we developed a novel exogenous cartilage lubricant (HAGO) with an excellent long-term wear resistance property by covalently grafting clinically used hyaluronic acid (HA) molecules onto graphene oxide (GO) nanosheets. The dispersion stability, antioxidant activity and biocompatibility of the HAGO were evaluated firstly. The reducing friction and resisting wear properties of the HAGO at bovine articular cartilage sliding counterface were then systematically investigated by using a pin-on-disk reciprocating friction tester. The wear resistance mechanism of the HAGO at cartilage friction interface was finally revealed through the worn surface characterizations combined with density functional theory calculation and molecular dynamics simulation. Results showed that the HAGO exhibited good biocompatibility, dispersion stability and anti-oxidative degradation ability. Compared with clinically used HA, the average friction coefficient and wear rate of cartilage surface lubricated by HAGO were reduced by 45 % and 85 %, respectively. It was worth noting that the cartilage surface lubricated by the HAGO showed no obvious macroscopic wear even after 60 min of the friction, indicating an excellent long-term wear resistance ability. Mechanism research revealed that the synergistic effect of the stable tribofilms and hydration lubrication layer formed by the HAGO targeting cartilage interface determined its long-term wear resistance efficacy. This study will provide new research ideas and an important theoretical basis for the development of a long-acting joint cavity injection lubricant for osteoarthritis. [Display omitted] •A novel exogenous cartilage lubricant of HAGO was developed for the osteoarthritis.•HAGO displayed excellent long-term wear resistance ability at the cartilage interface.•Synergistic mechanism of the stable tribofilms and hydration lubrication layer was proposed.